Amazon Plume Salinity Response to Ocean Teleconnections - Tyaquiçã, Pedro; Veleda, Doris; Lefèvre, Nathalie; Araujo, Moacyr; Noriega, Carlos; Caniaux, Guy; Servain, Jacques; Silva, Thiago (Frontiers in Marine Science, 2017)
Pacific and Atlantic sea surface temperature (SST) variability strongly influences rainfall changes in the Amazon River basin, which impacts on the river discharge and consequently the sea surface salinity (SSS) in the Amazon plume. An Empirical Orthogonal Function (EOF) analysis was performed using 46 years of SST, rainfall, and SSS datasets, in order to establish the relationship between these variables. The first three modes of SST/rainfall explained 87.83% of the total covariance. Pacific and Atlantic SSTs led Amazon basin rainfall events by 4 months. The resultant SSS in the western tropical North Atlantic (WTNA) lagged behind basin rainfall by 3 months, with 75.04% of the total covariance corresponding to the first four EOF modes. The first EOF mode indicated a strong SSS pattern along the coast that was connected to negative rainfall anomalies covering the Amazon basin, linked to El Niño events. A second pattern also presented positive SSS anomalies, when the rainfall was predominantly over the northwestern part of the Amazon basin, with low rainfall around the Amazon River mouth. The pattern with negative SSS anomalies in the WTNA was associated with the fourth mode, when positive rainfall anomalies were concentrated in the northwest part of South America. The spatial rainfall structure of this fourth mode was associated with the spatial rainfall distribution found in the third EOF mode of SST vs. rainfall, which was a response to La Niña Modoki events. A statistical analysis for the 46 year period and monthly anomaly composites for 2008 and 2009 indicated that La Niña Modoki events can be used for the prediction of low SSS patterns in the WNTA.